Surgical outcomes of anterior lumbar interbody fusion in revision lumbar interbody fusion surgery - Cheng-Min Shih; Cheng-En Hsu; Kun-Hui Chen; Chien-Chou Pan; Cheng-Hung Lee (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Backgrounds Anterior lumbar interbody fusion (ALIF) is an attractive option for revision lumbar interbody fusion as it provides wide access for implant removal and accommodation of large interbody grafts for fusion. However, revision lumbar interbody fusion surgery has not been found to result in significantly better functional outcomes compared with other approaches. To date, no prognostic factors of anterior lumbar interbody fusion in revision lumbar interbody fusion have been reported. In this study, we investigated the surgical results and possible prognostic factors of anterior lumbar interbody fusion in revision lumbar interbody fusion. Methods Patients who received revision interbody fusion surgery between January 2010 and May 2018 in our hospital were reviewed. Clinical outcomes were determined according to whether the VAS score improvement in back pain and leg pain reached the minimum clinically important difference (MCID) and Macnab criteria. Radiographic outcomes were assessed with fusion rate, preoperative, and postoperative lumbar lordosis. Operative-relative factors that may affect clinical outcomes, such as BMI, existence of cage migration, cage subsidence, pseudarthrosis, previous procedure, and number of fusion segments, were collected and analyzed. Results A total of 22 consecutive patients who received ALIF for revision interbody fusion surgery were included and analyzed. There were 9 men and 13 women with a mean age at operation of 56 years (26–78). The mean follow-up was 73 months (20–121). The minimal clinically important difference (MCID) was reached in 11 (50%) of the patients for back pain and 14 (64%) for leg pain. According to the modified Macnab criteria, 73% of the patients in this study had successful outcomes (excellent or good). The pain and lumbar lordosis had significant improvement (P < 0.05). Preoperative fusion segment ≥ 2 was shown to be a poor prognostic factor for back pain improvement reaching MCID (P = 0.043). Conclusions ALIF has proven effective for revision lumbar fusion surgery, yielding positive clinical and radiographic results. However, having two or more preoperative fusion segments can negatively impact back pain improvement. Level of evidence: IV.